ANALISIS FRAUDULENT FINANCIAL STATEMENT: PERSPEKTIF FRAUD HEPTAGON SEKTOR PERBANKAN BEI PERIODE 2021-2023 - Putri, Adelia Enggal; Susilo, Dwi Ermayanti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025, 2025)
Financial statement manipulation is a strategic issue in the banking sector that affects market stability, institutional credibility, and stakeholder trust. This study examines the influence of seven Fraud Heptagon factors on fraudulent financial statements in 54 financial service companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research adopts a descriptive quantitative approach with purposive sampling methods. The findings indicate that pressure and rationalization have a significant effect on the occurrence of fraud. These results suggest that the pressure to meet financial targets and individual moral justification are the main drivers of financial statement manipulation. Meanwhile, the variables of opportunity, competence, arrogance, culture, and religiosity show no significant influence on the dependent variable, indicating that internal controls and financial industry regulations have been relatively effective in mitigating fraud risks. This study highlights the importance of psychological aspects in fraud prevention and encourages the strengthening of internal monitoring systems, ethical education, and the development of an organizational culture that upholds integrity, professionalism, and transparency.